Arsenic (III) removal from aqueous solutions by mixed adsorbent - Singh A.P.; Srivastava K.K.; Shekhar H. (My University, 2025)
The removal of As(III) from its aqueous solutions by adsorption on homogeneous mixture of china clay and fly ash in equal proportions has been found to be dependent on various operating parameters such as concentration, temperature and pH. The As(III) removal is favourable at low concentration, high temperature and slightly basic condition at pH 8.0. The applicability of Langmuir isotherm in present system suggests the formation of monolayer coverage of As(III) molecules at the outer surface of the adsorbent. Thermodynamic parameters indicate the spontaneous and endothermic nature of the process. Adsorption kinetics studied using the model suggested by Lagergren infers a first order rate expression.